Unveiling the potential of Nd2O3 in optimizing the radiation shielding performance of B2O3–TiO2–BaO–ZnO-Nd2O3 glasses - Maryam Al Huwayz; Aljawhara H. Almuqrin; F.F. Alharbi; M.I. Sayyed; B. Albarzan (Nuclear Engineering and Technology)
This research focuses on the preparation of a new glass system designed specifically for applications in radiation shielding materials. These glasses are based on the general formula (56-x)B2O3–10TiO2–8BaO–27ZnO-(x-1)Nd2O3, where x takes the values of 2, 4, 6 and 8 mol%. For the examination of the designed glasses' radiation attenuation performance, Phy-X software was used, which is a useful approach for predicting the linear attenuation coefficient (LAC), the half value layer (HVL), and effective atomic number. The LAC decreases from 1.489 cm−1 to 0.551 cm−1 for the glass with x = 1 mol%, while the glass with 7 mol% Nd2O3 saw a decrease in the LAC from 2.483 cm−1 to 0.718 cm−1. Introducing Nd2O3 increases the glasses' LAC, suggesting enhanced radiation shielding performance. Also, Nd2O3 addition influences the HVL within the glasses, with higher content reducing the HVL. At 0.122 MeV, the HVL and tenth value layer (TVL) are 0.456 and 1.546 cm, respectively. At 0.245 MeV, the TVL is about 3.32 times higher than the HVL. The lowest mean free path (MFP) is found at 0.122 MeV, which varies between 0.672 cm for Nd1 and 0.403 cm for Nd4.